'A Horse-Race Is the Same All the World Over': The Cultural Context of Horse Racing in Native North America. Issue 3 (3rd March 2020) - Mitchell, Peter
Abstract: Native American horse racing has received little scholarly attention. Focussing on the Great Plains and the Southwest reveals that, far from being a diversion, it was a major focus for male competition for status and prestige. Since these concerns were at least as strong externally as internally, horse racing (and racehorse acquisition) formed part of a continuum of agonistic activities that also encompassed warfare. Moreover, the significance of races for the standing of individuals, men's societies, and tribal groups led to widespread use of protective medicines for enhancing equine performance and combating interference from opponents. Gambling formed part of this set of practices that collectively warrant describing Native American horse racing as a form of what Johan Huizinga termed 'sacred play'. For these reasons it encountered strong opposition from Euro-American authorities during the reservation era. Conversely, the persistence of Native American horse racing traditions via rodeo and Indian Relay racing attests to the enduring importance of the values they express. Opportunities exist for extending this preliminary assessment into a broader comparative study of Indigenous horse racing traditions across the post-1492 world.